1979
DOI: 10.1113/jphysiol.1979.sp012941
|View full text |Cite
|
Sign up to set email alerts
|

The responses of primary spindle afferents to fusimotor stimulation at constant and abruptly changing rates.

Abstract: SUMMARY1. Single fusimotor fibres to de-efferented soleus of the cat were stimulated to investigate the size and time course of the responses elicited in single primary spindle afferents. The muscle was kept at constant length close to the physiological maximum. Constant and alternating rates of fusimotor stimulation were used: (a) repetitive stimulation at constant rate (maintained stimulation); (b) modulated stimulation with the rate of activation alternating between two constant levels at repeat frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In support of this, Lennerstrand & Thoden (1968a, b) showed that static fusimotor stimulation was more effective than dynamic at supporting primary afferent firing during muscle shortening. It has also been shown (Hulliger, 1979) that static fusimotor stimulation is on average some 4-7 times more powerful than dynamic in producing changes in firing frequency of primary afferents. Recently, Appenteng, Prochazka, Proske & Wand (1982) have specifically tested the possibility of modulating fusimotor firing to keep primary afferent discharge constant during muscle shortening.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, Lennerstrand & Thoden (1968a, b) showed that static fusimotor stimulation was more effective than dynamic at supporting primary afferent firing during muscle shortening. It has also been shown (Hulliger, 1979) that static fusimotor stimulation is on average some 4-7 times more powerful than dynamic in producing changes in firing frequency of primary afferents. Recently, Appenteng, Prochazka, Proske & Wand (1982) have specifically tested the possibility of modulating fusimotor firing to keep primary afferent discharge constant during muscle shortening.…”
Section: Discussionmentioning
confidence: 99%
“…Normally static action should reduce and dynamic action should increase the afferent's dynamic sensitivity for length changes, even if fusimotor activity varies with time. Further, the direct excitatory action of static fibres is known to be considerably stronger than that of dynamic fibres (Hulliger, 1979). Hence, when static action prevails, the spindle is likely to act as a summer of reflex-shaped fusimotor and external length signals, with more 290 weight being given to the neural input.…”
Section: B Appelberg and Othersmentioning
confidence: 99%
“…The contribution of random noise to the error term is limited by the amount of averaging and by histogram resolution (cut-off at repeat frequency x No. of bins/2), and for recordings from I a afferents it tends to slightly increase with repeat frequency (reflecting the power distribution of noise in these recordings; for documentation see Hulliger, 1979, on a closely related application of r.m.s. error estimates).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…For a given response profile the r.m.s. error is proportional to the residual harmonic power contained in all Fourier coefficients beyond the fundamental (fitted sine; Hulliger et al 1977 a;Hulliger, 1979). The r.m.s.…”
Section: Data Collection and Analysismentioning
confidence: 99%